Psychosocial risk factors for Alzheimer's disease in Down syndrome patients and their association with brain changes: a narrative review - Hamadelseed, Osama; Elkhidir, Ibrahim H.; Skutella, Thomas (Preprints, 2022)
Several recent epidemiological studies attempted to identify risk factors for Alzheimer's disease. Age, family history, genetic factors (APOE genotype, Down syndrome), physical activity, and a low level of schooling are significant risk factors. In this review, we summarize the known psychosocial risk factors for the development of Alzheimer's disease in Down syndrome patients and their association with neuroanatomical changes in the brains of people with Down syndrome. We completed a comprehensive review of the literature on PubMed, Google Scholar, and Web of Science about psychosocial risk factors for Alzheimer's disease, for Alzheimer's disease in Down syndrome, and Alzheimer's disease in Down syndrome and their association with neuroanatomical changes in the brains of people with Down syndrome. Alzheimer's disease causes early pathological changes in Down syndrome patients, especially in the hippocampus and corpus callosum. The field needs more data about the neuroanatomical changes during childhood, how they change with increasing age, and the presence or absence of psychosocial risk factors. Further neuroimaging and psychosocial assessment-focused research is needed to understand the mechanisms leading to Alzheimer's disease at an early age and create more sensitive and relevant clinical, memory, and reasoning assessments for people with Down syndrome.